Effects of atorvastatin and aspirin on post-stroke epilepsy and usage of levetiracetam. Issue 50 (11th December 2020) - Zhao, Teng; Feng, Xuemin; Zhou, Chunkui; Ding, Ying; Lin, Weihong
Abstract: Objective: Atorvastatin and aspirin have been used in treating different forms of epilepsy. However, their effect on post-stroke epilepsy (PSE) still needs to be validated by large-scale clinical studies. In addition, their impact on the use of the antiepileptic drug levetiracetam for post-stroke epilepsy remains to be explored. Thus, the aim of this study was to further evaluate the effect of atorvastatin and aspirin on PSE and their effect on the usage of the antiepileptic drug levetiracetam in PSE patients. Methods: Patients, aged 65 to 85 years, with newly diagnosed post-ischemic stroke epilepsy from August 30, 2014 to August 30, 2018 were included in the study, with the exclusion of those with coexisting conditions. Results: Initially, 1321 patients were included, and 780 remained in the study at the 1-year follow-up. During the study, atorvastatin treatment with or without aspirin reduced the number of clinical epileptic episodes in PSE patients. It also reduced the dosage of levetiracetam and achieved better control of epilepsy compared to levetiracetam mono-treatment. Aspirin co-treatment with levetiracetam did not result in a significant improvement. However, the combination of aspirin with atorvastatin significantly reduced the number of seizures compared to atorvastatin treatment alone. Conclusion: Atorvastatin and aspirin co-treatment with levetiracetam can reduce epilepsy in PSE patients and reduce the dosage of levetiracetam required for effective control of PSE.